If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -11 = 10x + 13 Reorder the terms: -11 + 2x = 10x + 13 Reorder the terms: -11 + 2x = 13 + 10x Solving -11 + 2x = 13 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -11 + 2x + -10x = 13 + 10x + -10x Combine like terms: 2x + -10x = -8x -11 + -8x = 13 + 10x + -10x Combine like terms: 10x + -10x = 0 -11 + -8x = 13 + 0 -11 + -8x = 13 Add '11' to each side of the equation. -11 + 11 + -8x = 13 + 11 Combine like terms: -11 + 11 = 0 0 + -8x = 13 + 11 -8x = 13 + 11 Combine like terms: 13 + 11 = 24 -8x = 24 Divide each side by '-8'. x = -3 Simplifying x = -3
| (5)x*x+27x+10=0 | | (5)x*x+27+10=0 | | (x+6)(x+7)=(11+x)(4+x) | | 9-6*-.5=14+4*-.5 | | -3x+2(2x+4)=6(x+8)+15 | | 67x+25=350 | | -y=p | | x-0.2(x)=18 | | -5-(15y-1)=14y-32-y | | 5x(2x-10)=35 | | 6y^2+17y-3=0 | | 4z-6z+8z=6z | | 4(x-9)-3(x-15)=2x-3 | | 9-6x=14+4x | | 5x-7=x+3 | | 2x+14-(x+1)=0 | | (6)n*n+7n=20 | | (6)n*n+7n=0 | | 1x+10+8=4 | | 15-g=23-29 | | (6)n*n+7n-20=0 | | (6)n*n+7-20=0 | | 2x+4(x-6)=-11-5(x-4) | | 3x^4=1536x | | 5x+7=-7+2x+20 | | 3+7(x-9)=3x-4 | | 6+2x-(x-3)=4(x-1)+22 | | 2-5(x+1)=9+x | | 1x+4-3=18 | | (10)p*p-19p+7=0 | | 12x-30=-27 | | 29=2.75+1.75(x) |